Anticoccidial effect of Fructus Meliae toosendan extract against Eimeria tenella. (1st January 2020) - Yong, Ting; Chen, Meng; Li, Yunhe; Song, Xu; Huang, Yongyuan; Chen, Yaqin; Jia, Renyong; Zou, Yuanfeng; Li, Lixia; Yin, Lizi; He, Changliang; Lv, Cheng; et al.
Abstract: Context: Fructus Meliae toosendan extracts (FMTE) have a good therapeutic effect on coccidiosis, but there is no relevant research on its prophylactic effect on coccidiosis. Objective: This study comprehensively evaluates the anticoccidial effect of FMTE. Materials and methods: In vitro, the unsporulated oocysts were treated with serial dilutions of FMTE and incubated for 7 d, and the sporulated oocysts were counted for calculating the median lethal concentration (LC50 ) of FMTE. In vivo, 180 10-day-old broiler chickens free of coccidiosis were weighted and randomly distributed into six groups: normal group, untreated group, 4 protective groups (positive group and three FMTE groups). From day 10 to day 21, chickens in the three FMTE groups were pre-treated with FMTE at the dosage of 2.5, 5 and 10 g/kg/d, respectively, and chickens in the positive group were pre-treated with qiuliling (10 g/kg/d). On day 14, chickens in all groups except the normal group were orally infected with 1.5 × 10 4 sporulated oocysts. The clinical symptoms were observed from day 10 to day 21, the anticoccidial index (ACI), tissue lesions, and intestinal microflora were determined on day 21. Results: FMTE showed anti-sporulation effect against E. tenella and the LC50 value was 245.83 µg/mL in vitro . In vivo, FMTE at the dosage of 10 g/kg/d was effective against E. tenella infection, and its ACI value was 162.56, which was higher than the value of positive drug qiuliling (128.81). Discussion and conclusions: FMTE have potent anticoccidial effects, and it presents an alternative anticoccidial agent for avian coccidiosis control.